2017
DOI: 10.1167/iovs.17-21973
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neurotrophins and Inflammatory Mediators in Vitreous of Patients With Diabetic Retinopathy

Abstract: PurposeTo assess vitreous levels of inflammatory cytokines and neurotrophins (NTs) in diabetic retinopathy (DR) and elucidate their potential roles.MethodsA prospective study was performed on 50 vitreous samples obtained from patients with DR (n = 22) and the nondiabetic controls (n = 28). All patients were candidates for vitrectomy. Inflammatory cytokine and NT levels were determined with ELISA. Potential source and role of NTs was determined by using human retinal Müller glia and mouse photoreceptor cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(144 citation statements)
references
References 43 publications
5
134
0
5
Order By: Relevance
“…TNF-a upregulation is involved in many diseases as oxidative signaling in angiogenesis. 28 Upregulation of inflammatory cytokines such as TNF-a is implicated in the pathogenesis of DR. 29 As expected, we found that electrical stimulation of the ICN caused a temporary reduction in choroidal blood flow due to vasoconstriction, as well as mydriasis resulting from adrenergic effects on the iris dilator muscle. Other studies in rat have reported decreased uveal blood flow following acute cervical sympathetic trunk stimulation, an effect mediated exclusively by a 1 -ARs.…”
Section: Discussionsupporting
confidence: 85%
“…TNF-a upregulation is involved in many diseases as oxidative signaling in angiogenesis. 28 Upregulation of inflammatory cytokines such as TNF-a is implicated in the pathogenesis of DR. 29 As expected, we found that electrical stimulation of the ICN caused a temporary reduction in choroidal blood flow due to vasoconstriction, as well as mydriasis resulting from adrenergic effects on the iris dilator muscle. Other studies in rat have reported decreased uveal blood flow following acute cervical sympathetic trunk stimulation, an effect mediated exclusively by a 1 -ARs.…”
Section: Discussionsupporting
confidence: 85%
“…31 In addition, Müller glia is not only a source of neurotrophins within the retina but also respond to neurotrophins as they express all the neurotrophin receptors. 41 Release of neurotrophins from Müller glia can also be promoted by other neurotrophins, 42 inflammatory cytokines, 43 as well by activated microglia. 30 However, this response appears to be selective, as microglia conditioned media increases the Müller glia expression of mRNA coding for BDNF, but does not modify the expression of NGF, NT-3, CNTF.…”
Section: Müller Glia Are An Important Source Of Neurotrophins Withinmentioning
confidence: 99%
“…Elevation in systemic and local chemokine concentration is present in patients suffering from DR (Petrovic et al, ; Koleva‐Georgieva et al, ; Suzuki et al, ). Several authors could demonstrate increased levels of TNF‐α, IL‐8, CCL2, IL‐1β, and IL‐6 in the vitreous fluid (Demircan et al, ; Murugeswari et al, ; Boss et al, ). Furthermore, peripheral monocytes from DR patients secrete high amounts of IL‐1β, IL‐6, TNF‐α, IL‐8, and IL‐1ra (Hatanaka et al, ; Bradshaw et al, ).…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%